THE EFFECT OF NETWORK COMMUNITY BASED TOURISM IMPLEMENTATION ON INCREASING INDEPENDENCE AND INCOME (STUDY ON THE TOURISM VILLAGE OBJECT OF SITU LEBAK WANGI, PARUNG DISTRICT, BOGOR REGENCY) - Okky Rizal Ridwan; Elly Malihah; Rini Andari (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2022)
This study aims to determine the impact of implementing network community based tourism on the increase and income carried out in the tourist village of Situ Lebak Wangi, Bogor. This research is conducted using a quantitative approach with a causality model to test the proposed hypothesis. The entire community in Pamegarsari Village, Parung District, Bogor is the population in this study. The sample in this study amounted to 100 samples obtained through a survey of accidental sampling technique. Based on the research conducted, it is found that Network Community Based Tourism has a significant positive effect on the independence and income of citizens of the Situ Lebak Wangi Area. Community independence can increase when there is community-based tourism development. Community-based tourism management makes its management involve a lot of the community. The community is provided with business stalls in the Lebak Fragrant Lake area to invite tourists while growing the economy of the local residents.